Challenging Islamophobia by Action (An Overview of the Islamic Activist Movement in America from A Fiqh Aqalliyāt Perspective) - Khalik, Subehan; Hj Rofie, Mohamad Khadafi; Usman, Ummi Farhah; Nur Wulan Rohimah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2024)
The issue of Islamophobia and the treatment of minorities is deeply rooted in the culture of Muslim societies. Throughout history, Islamic constitutional law has focused on the treatment of minority groups. However, the meaning of